Maternity handover in Kerala: a cross sectional study - Aadil Sheikh; Jessica Dunphy; Claire Humphries; Christina MacArthur and Semira Manaseki-Holland (International Journal of Community Medicine and Public Health, 2018)
Background: The objective of the study was to explore the referral system from the community to hospital obstetric care in Kerala, India. Methods: Cross-sectional study. A total of 206 obstetric inpatients in 3 hospitals in Kerala, India completed an orally-administered questionnaire regarding referral and attitudes towards healthcare information. Results: Among 206 respondents, 19 (9%) had been referred from another healthcare provider. In multivariate analysis, referral was independently associated with being in a tertiary hospital (p<0.001). At total of 17 referred women received a document containing hand-written notes from their previous healthcare provider. Just 3 of the documents available to view were formal referral documents; others were test results and/or hospital notes. A total of 170 (86%) of the 206 women thought that receiving documents such as referral letters was important; mostly because it helped them understand their condition and explain it to others (91%). Conclusions: A high rate of self-referral (91%) was reported by obstetric inpatients. It appears that some women who are referred do not receive a formal referral document. Participants thought that receiving referral documents was important. A strong health system requires transfer of information between primary and secondary/tertiary care services, which India is seeking to develop. Further research is needed into why women are not accessing community health services and the impact of the content of referral documents on patient care